2010
DOI: 10.1089/thy.2010.0015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of a Cytomorphological Subclassification of Follicular Patterned Thyroid Lesions: A Study of 927 Consecutive Cases with Histological Correlation

Abstract: This study supports the National Cancer Institute consensus showing a different risk of malignancy for "follicular lesions of undetermined significance” compared with "follicular neoplasms" and "Hurthle cells neoplasms," which are more suspect for malignancy. This subclassification could improve clinical management of thyroid nodules, helping to better select patients for surgery or follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
4
26
1
Order By: Relevance
“…Thirteen studies in the pre-TBSRTC [13,14,15,16,17,18,19,20,21,22,23,24,25] and 8 studies in the post-TBSRTC [11,26,27,28,29,30,32,33] provided the specific histopathological diagnoses for their cases with malignant follow-up, and these are detailed in table 3. From this data, the rate of the follicular variant of papillary thyroid carcinoma (FV-PTC) as a fraction of all malignancy was equivalent, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies in the pre-TBSRTC [13,14,15,16,17,18,19,20,21,22,23,24,25] and 8 studies in the post-TBSRTC [11,26,27,28,29,30,32,33] provided the specific histopathological diagnoses for their cases with malignant follow-up, and these are detailed in table 3. From this data, the rate of the follicular variant of papillary thyroid carcinoma (FV-PTC) as a fraction of all malignancy was equivalent, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The same approach has most frequently been adopted in almost all similar studies Ho et al, 2014;Hyeon et al, 2014;Nikiforov et al, 2014;Rago et al, 2014;Deniwar et al, 2015;Yoo et al, 2015), even when a second FNAB was performed (Ho et al, 2014;Rosario, 2014;Yoo et al, 2015). For our Thy 3 nodules, surgery allowed us to ascertain a low rate of thyroid cancers (19%), which is a percentage close to that reported in studies employing the BTA classification (Mihai et al, 2009;Deandrea et al, 2010;Giusti et al, 2014;Rago et al, 2014). In our study, the reclassification of Thy 3 nodules according to BTA 2014 criteria identified a significantly higher incidence of Hurtle adenomas in Thy 3f than in Thy 3a, without a very significant difference between the two sub-categories in the risk of malignancy on histology.…”
Section: Discussionmentioning
confidence: 51%
“…Deandrea et al (2010) stratified 294 Thy 3 nodules, for which the malignancy rate was 17%, into three categories: "follicular lesion of indeterminate significance", "follicular neoplasm", and "Hurtle-cell neoplasm". They found that the percentage of malignant cases in each category was significantly different (5%, 25%, and 23%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study by Deandrea et al, further classifying the Thy 3 lesions improved diagnostic accuracy. The proportions of cancers in each group were Thy 3a ("follicular lesions of indeterminate significance"), Thy 3b ("follicular neoplasm") and Thy 3c ("Hurthle-cell neoplasm") 4.95%, 25.0% and 22.77% respectively (24). Various modalities are being tried to improve the diagnostic accuracy in Thy 3 nodules and reduce the rates of diagnostic lobectomy -for example PET scan, molecular markers, oncogene detection, and ultrasound elastography.…”
Section: Discussionmentioning
confidence: 99%